COPYRIGHT PROTECTION OF WAYANG KULIT AS A TRADITIONAL INDONESIAN CULTURE - An Arafahan; Saidin; Faradila Yulistari Sitepu (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
This study aims to understand how the Indonesian government and people work to preserve art that has become an integral part of the Indonesian state and nation, especially wayang kulit and the history of wayang itself. This study was done by library research as a research method. In this regard, the study utilizes a variety of connected or relevant sources, including books, journals, magazines, documents, and others, as well as common law jurisdictions such as Law No. 28 of 2014 pertaining to Copyright. The findings reveal that wayang kulit as a traditional Indonesian culture has been legally protected by the state in accordance with Copyright Law no. 28 of 2014 (UUHC), which is irreversible and has been registered by the government at the Convention for the Safeguarding of the Intangible Cultural Heritage on November 7, 2003, so that it can be preserved and protected from claims by other countries as their own culture. It is hoped that in the future, by being protected by law, the Indonesian people will be able to maintain and preserve wayang kulit so that they do not become extinct and are not claimed by other nations.